Biomassa e estoque de nutrientes em Eucalyptus urophylla x Eucalyptus grandis em área arenizada do bioma Pampa - RS - Frantz, Bernardo Corso (2016)
In Rio Grande do Sul, the Eucalyptus commercial plantations are spread over various regions and occupy the most diverse soil compositions, many of which have good fertility, leading to high growth rates in the stands. The challenge, however, is improve the productivity in low quality sites where the soil fertility by its deficiency can generate environmental problems. In this context, the present work is inserted to increase the understanding of forest nutrition in these sites. This study aimed to characterize nutritionally a stand of hybrid Eucalyptus urophylla x Eucalyptus grandis planted in degraded area of the Pampa biome. The soil in the study area is classified as a Quartzarenic Neosoil. For the dendrometric parameters were installed at random, five sample plots. For sampling of biomass and nutrient stocks were felled twelve trees, three by diameter class. Total aboveground biomass was 36.24 Mg ha-1. The average distribution for biomass components was 62% wood, 20% branch, 11% leaf and 7% bark. The total stock of macro and micronutrients in aboveground biomass was 463.2 kg ha-1 and 20.0 kg ha-1, respectively. The largest amount of N was found in the leaves and the largest amounts of P and K was found in the wood. The highest values of biological utilization coefficient (CUB) were found in the wood component, with the exception of S, which was found in the component branches. The harvest of only the wood component involves the removal of 24.1% N; 33.9% P; 46,3 K; 10.9% Ca; 15.2% Mg; 48.1% S; 17.4% B; 42.4% Cu; 35.9% Fe; 12.9% Mn and 48.9% Zn, representing the simulation with a lower nutrient removal, which is the most suitable from the point of view of nutritional ecosystem sustainability.